Pemahaman Konsep Matematika Siswa Kelas III di Sekolah Dasar Surabaya Materi Pecahan Berbantu Media Folding Paper - Kunti Dian Ayu Afiani; Meirza Nanda Faradita (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
This article aims to examine students' understanding of concepts in learning mathematics with the help of Folding Paper, the study in this article focuses on three factors, namely: Results of interviews with teachers of understanding mathematical concepts, results of observations of understanding mathematical concepts and the results of applying the RME learning model to fractional material. The method in this research uses descriptive qualitative. Sources of data consist of interviews with teachers, observations and tests. For data analysis techniques using quantitative and descriptive qualitative data analysis. From the results of interviews, observations and tests that students' understanding of mathematical concepts is still relatively low.